Impact of Green Supply Chain Management on Economic and Organizational Performance of Food Industry in Sindh and Punjab - Siddiqui, Muhammad Iqbal Ahmed; Siddiqui, Danish Ahmed (CenRaPS Journal of Social Sciences, 2020)
The aim of this study to investigate the impact of green supply chain practices from the management decision-making level to the implementation of the food industry. We hypothesized that positive Institutional and Leadership Pressures would lead to external and internal Green Practices, which would in turn makes the organizational as well as economic Performance better. Institutional performance seems to have a positive and significant effect on external green practices, however, affect negatively to internal practices. Leadership pressure also has a negative effect on external green collaborations. Both internal and external factors also seem to have a positive and significant effect on both organizational and economic performance. As expected, economic performance seems to affect organizational performance, moreover, external Green Collaboration also affect Internal Green Practices, positively. Organizations and decision-makers of the food industry are provided with detailed insight into implementing a green supply chain, from multiple perspectives of the organization, which may help the decision-makers in formulating the strategies. It is a novel attempt to assess the organizational and economic performance of the food industry in Pakistan, using a modified version of the Ahmed & Najmi model, as it shed light for the first time on how institutions and leadership can influence the performance of the food industry through green practices.